2016
DOI: 10.18632/oncotarget.12530
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of polymorphisms in H19 lncRNA and cancer risk: a meta-analysis of 13,392 cases and 18,893 controls

Abstract: H19 refers to a long non-coding RNA (lncRNA) that functions as an oncogenic molecule in different cancer cells. Genetic variants of H19 may affect the activity of certain regulatory factors, which subsequently regulate the aberrant expression of H19. This feedback loop might be one of the underlying mechanisms influencing tumour susceptibility and prognosis. Although there have been several recent studies that examined possible links between polymorphisms in H19 and cancer risk, the results have been inconclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 23 publications
3
28
0
Order By: Relevance
“…However, this result could not be repeated in the subsequent studies by Li and Hua et al, which reported an increased cancer risk for rs217727 [20,39]. Thus, in 2016, Chu et al performed a meta-analysis involving 5 articles with 7110 subjects that indicated no correlation between rs217727 and overall cancer risk [49]. Compared with previous meta-analysis, we led to an opposite conclusion that rs217727 polymorphism was significantly associated with increased cancer susceptibility, especially in the Asian population.…”
Section: Discussionmentioning
confidence: 97%
“…However, this result could not be repeated in the subsequent studies by Li and Hua et al, which reported an increased cancer risk for rs217727 [20,39]. Thus, in 2016, Chu et al performed a meta-analysis involving 5 articles with 7110 subjects that indicated no correlation between rs217727 and overall cancer risk [49]. Compared with previous meta-analysis, we led to an opposite conclusion that rs217727 polymorphism was significantly associated with increased cancer susceptibility, especially in the Asian population.…”
Section: Discussionmentioning
confidence: 97%
“…Based on our preliminary ndings, we targeted four lncRNAs, lncMALAT1, lncHotair, lncH19, and lncNeat1 to determine which of these lncRNAs are involved in processes underlying in ammation attenuation [17][18][19][20]. RT-PCR was conducted to determine lncRNA levels following treatment with IL-1beta and Dex.…”
Section: Veri Cation Of the Lncrnas Involved In In Ammation Attenuationmentioning
confidence: 99%
“…For instance, it was shown that the lncRNA level was reduced by allelic changes in 3 BioMed Research International rs11752942 through binding micro-RNA, leading to increased esophageal squamous cell proliferation [15]. Different genetic variants of H19 are able to regulate the aberrant expressions of H19 and influence the activity of regulatory factors [16]. Many previous studies have corroborated the significant role of H19 as an oncogenic molecule in different cancer cells and in tumorigenesis.…”
Section: Discussionmentioning
confidence: 98%
“…To date, various studies have shown the association between H19 polymorphisms and several types of cancer. In a meta-analysis, Chu et al reported the association between three H19 polymorphisms (rs2839698, rs217727, and rs2107425) and cancer susceptibility [16]. It was also shown that the polymorphic site of rs217727 on H19 was associated with the risk of breast cancer (OR = 0:79; 95%CI = 0:55 − 0:97) [23].…”
Section: Discussionmentioning
confidence: 99%